1999
DOI: 10.1038/sj.cr.7290020
|View full text |Cite
|
Sign up to set email alerts
|

Random amplified polymorphic DNA analysis of eel genome

Abstract: Eel family is a huge one, in which many kinds of eels especially some migratory eels, bear strong resemblance to each other, and are therefore difficult to be identified. In this study 29 random primers were used to make RAPD analysis for Japanese eel (Anguilla japonica), European eel (Anguilla anguilla) and Pike eel (Muraenesox cinereus). And totally 299 fragments were counted. Shared or specific fragments were counted and genetic similarity or genetic distance were calculated. The genetic similarity between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, more researches will also be necessary to identify the discrimination between/among populations and species, using an annealing control primer system. From what has been said above, the potential of this analysis to ascertain diagnostic markers for the identification of three eel species has also been verified ( Tasanakajon et al, 1998 ; Jing & Li, 1999 ; McCormack et al, 2000 ; Kimura et al, 2004 ; Kim et al, 2006 ; Yoon, 2008 ). It was reported that the species relation-ships revealed by the PCR approach should be consistent with previously obtained data using morphological portrait ( Nebauer et al, 2000 ).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, more researches will also be necessary to identify the discrimination between/among populations and species, using an annealing control primer system. From what has been said above, the potential of this analysis to ascertain diagnostic markers for the identification of three eel species has also been verified ( Tasanakajon et al, 1998 ; Jing & Li, 1999 ; McCormack et al, 2000 ; Kimura et al, 2004 ; Kim et al, 2006 ; Yoon, 2008 ). It was reported that the species relation-ships revealed by the PCR approach should be consistent with previously obtained data using morphological portrait ( Nebauer et al, 2000 ).…”
Section: Resultsmentioning
confidence: 80%
“…As the eel culture industry grows, so doe’s interest into the genetics of this finfish species. However, in spite of their economic and scientific consequences, a little information currently exists regarding the genetic levels only of eel species in Korea and/or the other countries ( Min & Yang, 1993 ; Jing & Li, 1999 ; Kimura et al, 2004 ; Oh, 2011 ). In this study, to explicate the genetic distances and differences among geographical eel species, the author accomplished a clustering analysis of three eel species collected from the Yellow Sea.…”
Section: Introductionmentioning
confidence: 99%